Delegitimizing COVAX? A study of Sub-Saharan’s African leaders’ public statements - Skantze,Alicia (2022)
The Covid-19 pandemic has been devastating across the globe, not the least for countries already struggling with insufficient health systems and a lack of medical resources. As soon as the crisis hit vaccines started being developed and seen as a way to get out on the other side, and with new techniques multiple vaccines quickly became effective. However, the distribution of these vaccines soon became an issue of inequality. This research paper will look at public statements made by sub-Saharan African leaders and their response to the global initiative COVAX, created by the World Health Organization. This Public-Private Partnership created grand goals for equitable global distribution of vaccines. However, the results of COVAX has arguably not lived up to the ambitions with several countries in Africa still waiting to receive their first dose. This paper contributes to the vast volume of literature looking at the global management of the Covid-19 pandemic and the inequalities it highlighted. The public statements analyzed shows four major themes; the different tone made in comments, the concern for tremendous inequalities, the lack of sufficient quality in vaccines, and call for more action. By analyzing statements from African leaders using theories on hegemony and legitimization the findings indicate that COVAX reinforces the unequal structures between the global north and the global south. Ultimately, this can be part of the research helping us understand the failures and successes of this pandemic and we can learn from our mistakes and improve the global community responses and actions to ensure everyone's right to healthcare and vaccines.
Keywords: COVAX; public statements; (de)legitimization; sub-Sharan Africa; public-private partnership; global inequalities; Covid-19 vaccines